Wear Properties of TiC-Reinforced Co50 Composite Coatings from Room Temperature to High Temperature - Nga Thi-Hong Pham; Van-Thuc Nguyen (Advances in Materials Science and Engineering)
In this paper, the laser cladding is created by using Co50 powder and TiC mixture, covering a H13 hot-working steel substrate. The samples are analyzed by the hardness test, XRD, SEM, and friction test to identify the forming phases, microhardness distribution, and wear-resistant characteristics. The results indicated that hardness reduces from the coating zone to the substrate, achieving the highest value at the coating zone. Increasing the content of TiC results in improving the coating hardness. The coatings with 10%–20% TiC show high-quality surface morphology and macrograph. With 30% TiC, the hardness obtains a higher hardness, but the surface appears to crack. The microstructures of the coatings present a well-mixed and well-distribution of the TiC particle on the Co matrix. The friction coefficient of H13 steel and Co50 coating reaches the maximum value when the load is 50 N and mostly decreases with the increase in the load. The wear rates of H13 steel and Co50 coatings mainly increase with the increase in the load. The temperature has a greater influence on the friction coefficient of the Co50 coating. However, the temperature has a small effect on the friction coefficient of the 20% TiC coating. The wear resistance of 20% TiC coating is higher than that of H13 steel, Co50 coating, and 10% TiC composite coating. At room temperature, the wear mechanism of the coating is mainly brittle spalling, adhesive wear, and ploughing. At 700°C, the wear mechanism is mostly oxidation wear and fatigue wear. After laser cladding, the service life of the coated surface could be greatly improved. The Co + 20% TiC coating has high hardness and wear resistance.